2008
DOI: 10.21273/jashs.133.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wide Hybridization on Highbush Blueberry Breeding

Abstract: The use of interspecific hybridization in blueberry (Vaccinium L. section Cyanococcus Gray) breeding has resulted in the incorporation of novel traits from wild germplasm and the expansion of the geographic limits of highbush blueberry (V. ×corymbosum L.) production. The objectives of this study were: 1) to estimate the impact of wide hybridization on inbreeding, heterozygosity, and coancestry of the cultivated tetraploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 30 publications
6
59
0
Order By: Relevance
“…In addition, transgenic 'Legacy' plants with herbicide resistance have been produced and field trials have been carried out (Song et al 2007(Song et al , 2008. However, with the wide differences in genetic composition of southern highbush cultivars (Brevis et al 2008;Ballington 2009), systematic studies are still needed to optimize regeneration systems for individual cultivars. In the present study, we developed efficient regeneration systems for four selected southern highbush cultivars using leaf explants and found that both cultivar source and physiological status of leaf explants affected shoot regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, transgenic 'Legacy' plants with herbicide resistance have been produced and field trials have been carried out (Song et al 2007(Song et al , 2008. However, with the wide differences in genetic composition of southern highbush cultivars (Brevis et al 2008;Ballington 2009), systematic studies are still needed to optimize regeneration systems for individual cultivars. In the present study, we developed efficient regeneration systems for four selected southern highbush cultivars using leaf explants and found that both cultivar source and physiological status of leaf explants affected shoot regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is important to characterize the existing breeding selections before they are released or used in crossing. Southern highbush blueberry possesses genes introduced from several Vaccinium species (Brevis et al, 2008). Two tested accessions of V. arboreum displayed immunity against T. minima.…”
Section: Discussionmentioning
confidence: 99%
“…Southern highbush blueberry cultivars possess genes introduced from several Vaccinium species, including V. darrowii Camp, V. angustifolium Ait., V. virgatum Ait., V. elliottii Chapm., V. tenellum Ait., V. pallidum Ait., V. myrsinites Lam., and V. stamineum Lam. (Brevis et al, 2008;Ehlenfeldt et al, 1995;Hancock et al, 1995;Yousef et al, 2014). Relatively little is known about the reaction of commercial blueberry cultivars and native diploid Vaccinium species to T. minima.…”
mentioning
confidence: 99%
“…V. angustifolium is well adapted to colder climates, is low maintenance with low agrochemical input requirements because of its high degree of pest resistance, and is well suited to mechanical harvesting (Janes and Percival, 2003;Yarborough, 2012). Hexaploid cultivars belonging to V. ashei have greater plant vigour and yield, tolerance of a wider range of soils, and greater fruit firmness, giving longer shelf-life of harvested fruit (Brevis et al, 2008).…”
Section: Introductionmentioning
confidence: 99%